Iguratimod as a New Drug for Rheumatoid Arthritis: Current Landscape - Xie, Sisi; Li, Shu; Tian, Jing; Li, Fen (Frontiers in Pharmacology, 2020)
Iguratimod (IGU) is a novel synthetic small molecule disease modified anti-rheumatic drug approved only in Japan and China up to date. IGU plays an important immunomodulatory role in the synovial tissue of rheumatoid arthritis by inhibiting the production of immunoglobulins and cytokines and regulating T lymphocyte subsets. IGU also regulates bone metabolism by stimulating bone formation while inhibiting osteoclast differentiation, migration and bone resorption. In clinical trials, IGU was shown to be superior to placebo and not inferior to salazosulfapyridine. Combined therapy of IGU with other disease-modifying anti-rheumatic drugs showed significant improvements for disease activity. IGU has good efficacy and tolerance as an additional treatment for rheumatoid arthritis patients with inadequate response to methotrexate and biological disease-modifying anti-rheumatic drugs. In this review, we summarize current landscape on the mechanism of action of IGU and its clinical effectiveness and safety. It is expected that further translational studies on IGU will pave the road for wider application of IGU in the treatment of autoimmune diseases other than rheumatoid arthritis.